Short-term residual effects of occasional tillage on crop performance, soil water, and water-use efficiency in a 10-year no-till system under a dry Mediterranean climate - Diop, Massamba; Beniaich, Adnane; Cicek, Harun; Ouabbou, Hassan; Bamouh, Ahmed; El Gharras, Oussama; Dahan, Rachid; Zine El Abidine, Aziz; El Gharous, Mohamed; El Mejahed, Khalil (Frontiers in Sustainable Food Systems, 2024)
A study was carried out in an on-farm field trial set up in Meknes (Morocco) under a long-term no-till (NT) system to evaluate the residual effect of one-time occasional tillage (OT) on crop performance, soil water, and water-use efficiency (WUE) one and two years after OT implementation. Shallow and deep options of OT were compared with common NT practices (with crop residue retention and with crop residue removal) for two consecutive seasons of 2021-2022 (year 1) and 2022-2023 (year 2). The four tillage practices were implemented in November 2020. Three crops were studied each year: durum wheat (Triticum durum), faba bean (Vicia faba minor), and chickpea (Cicer arietinum) all grown under NT in both the years and arranged in four crop rotations. Our findings show that grain yield of wheat and chickpea was negatively affected by OT for all years considered. In wheat, there was a grain yield loss of 18 and 20 % for shallow and deep OT, respectively compared to NT with crop residue retention. In chickpea, the grain yield loss was as high as 47 and 49 % for shallow and deep OT respectively. Average soil water storage measured at 0-60 cm at sowing was also lower in deep OT (133 mm) compared to NT with crop residue retention (151 mm) for all years and rotations considered. Yet, in wheat year 1, deep OT slightly improved soil water content at 30 cm depth compared to NT treatments. The comparison of WUE between treatments showed that, under NT with crop residue retention, the crops produced more grain and aboveground biomass per mm of water. Wheat/faba bean rotation had a greater grain yield and WUE (all years considered) and overall greater soil water content (year 1), compared to the wheat/chickpea rotation. The results suggest that the effects of OT on crop performance and water productivity in the short term can be adverse. On the other hand, grain yield of wheat can be improved by a judicious choice of legume to be used as a preceding crop.